STRATEGY FORMULATION TO IMPROVE PERFORMANCE OF UD.ADITYA MEUBEL IN NORTH BOLAANG MONGONDOW (THE IMPLEMENTATION OF QSPM AND TOPSIS MODEL) - Yumikesari, Syafitri .; Saerang, David P.E; Tumewu, Ferdinand J (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Since inaugurated as a regional autonomy on 2 January 2007, the development of Â North Bolaang Mongondow area is developed rapidly. The tendency of development will be on and on along with the opening of new land in this area. By the increasing of public demand for furniture products then it will automatically increasing the number of companies engaged in this same field of industry. This research has the purpose to concerning MSMEs UD. Aditya Meubel is chosen as the main research object by considering its existence since the invention in 2007 until now. By doing strategic management process which is strategy formulation, then this could help the business in improving the performance so that they can survive and remain consistent to its goal, which is also automatically, can help to increase the revenue. The research method used is the combination of descriptive qualitative and quantitative method where quantitative is used to facilitate the qualitative by using some of the analytical tools such as IFE, EFE, IE, SWOT,QSPM and TOPSIS .The result on QSPM and Fuzzy TOPSIS show that the market development becomes the top preferred priority among other alternative strategies with the amount of weight is 3.697 in QSPM and 0.72124 in Fuzzy TOPSIS. Thus, UD. Aditya Meubel needs to expand its marketing area gradually, which can be started in 5 areas around its regular marketing area.Â Keywords: strategic management, strategy formulation, ife, efe, swot, internal-external matrix, qspm, topsis model.